1997
DOI: 10.1111/j.1365-2249.1997.499-ce1398.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against dengue virus E protein peptide bind to human plasminogen and inhibit plasmin activity

Abstract: SUMMARYBoth mice and rabbits immunized with dengue virus E protein peptide spanning amino acids 100-119 (D4E) produced antibodies that reacted not only with the D4E peptide itself but also with human plasminogen, as shown by ELISA and Western blot. Sera from dengue virus-hyperimmunized mice and dengue patients also contained antibodies against D4E and plasminogen. Furthermore, such sera all contained plasmin inhibitory activity. Using affinity-purified anti-D4E antibodies and free D4E peptide for competitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 19 publications
0
15
1
Order By: Relevance
“…Unlike previous studies that have shown that D4E peptide (E protein aa 100-119) can inhibit binding of dengue patients' Abs to Plg peptide PL + (13,15), ,20% of Ab binding to Plg was inhibited by a synthetic peptide of E protein aa 96-110 (MK peptide) (Fig. 1C).…”
Section: Abs Cross-react To Plg In Denv Patients' and Immunized Mice contrasting
confidence: 74%
See 3 more Smart Citations
“…Unlike previous studies that have shown that D4E peptide (E protein aa 100-119) can inhibit binding of dengue patients' Abs to Plg peptide PL + (13,15), ,20% of Ab binding to Plg was inhibited by a synthetic peptide of E protein aa 96-110 (MK peptide) (Fig. 1C).…”
Section: Abs Cross-react To Plg In Denv Patients' and Immunized Mice contrasting
confidence: 74%
“…Autoantibodies against DENV E, NS1, and prM proteins found in DHF/DSS patients can cross-react with different cells such as endothelial cells and platelets, which can lead to cell damage or platelet activation (15,(19)(20)(21)(22). In this study, we found Plg crossreactive Abs in dengue patients from both Kaohsiung (mainly DENV type 2 infection in adult patients) and Vietnam (mainly DENV type 3 in infants).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Monoclonal anti-NS1 antibodies were reported to cross-react with thrombocytes, endothelial cells and human clotting factors, such as fibrinogen [10] . In addition, anti-E antibodies were also reported to bind to plasminogen and inhibit plasmin activity [19][20][21] . In this study, we demonstrated that except anti-NS1and anti-E antibodies, anti-prM antibody could be an autoantibody and may cross-react with epithelial cells, kidney cells, endothelial cells and even T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%